Wzniosłość i potoczność w pismach bł. siostry Bernardyny Marii Jabłońskiej - Nowak, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents language idiosyncracies of Sr. Bernardina Maria Jabłońska (187-1940), co-founder of the Congregation of Albertine Sisters Serving the Poor (ZSAPU). Sr. Bernardina Jabłońska’s variable feature of religious idiostyle is a combination of sublime qualities (which may be embodied as poetic) and colloquial style. Sublimeness is achieved primarily through artistic means, mainly comparisons and metaphors. Colloquialism is represented by diminutive and hypocoristic formations, lexical and phraseological colloquial expressions (including colloquial comparisons), and quasi-dialogical syntactic constructions.